Ruptura do Manguito Rotador: tratamento baseado em exercícios, avaliação de ensaios clínicos na literatura e apresentação clínica no pós-cirúrgico - Ribeiro, Larissa Pechincha (2023)
Among the most common diagnoses in patients with shoulder pain are rotator cuff (RC) tears. Although conservative exercise-based treatment as suggested as first line in the management of individuals with RC tears, there is no consensus or evidence to suggest an exercise program for his population and many patients opt to do surgical tendon repair. Thus, it is important that the literature presents sufficient detail to facilitate the implementation of the studies’ findings in clinical practice, and also to understand which factors can influence patient satisfaction with the shoulder to help better clinical outcomes. This thesis is composed of three studies: Study 1: Objective: To compare two exercise-based treatment programs for individuals diagnosed with RC tears. Methods: Subjects with shoulder pain and diagnosis of atraumatic and degenerative RC tear participate in this controlled, randomized and blind clinical trial. One group performs an exercise with no emphasis on the RC and the other group performs exercise program with emphasis on the RC. The primary outcome is quality of life. Patients receive treatment for 12 weeks (2x/week). Results and conclusion: So far, 34 patients have been randomized. Partial analyzes are not appropriate until completion of the study. We expect to offer scientific bases that can help physiotherapists in the management of individuals with RC tear. Study 2: Objective: To evaluate description and fidelity of clinical trials with exercise-based treatment for the population diagnosed with RC tears. Methods: A scoping review was carried out through a systematic search in 8 databases (PubMed, Embase, CINAHL, LILACS, Cochrane, Web of Science, SCOPUS e SciELO). Clinical trials performed in individuals with RC tears confirmed by imaging were included. All studies should have offered some exercise-based treatment. The methodological quality of the studies was assessed using the PEDro scale (Physiotherapy Evidence Database scale). The TIDieR checklist (Template for Intervention Description and Replication) was used to evaluate the description, and the NIHBCC, (National Institutes of Health Behavior Change Consortium) to evaluate the fidelity of the implementation. Results and conclusion: Despite the adequate methodological quality of the studies, the description of interventions and the fidelity of implementation are reported unsatisfactorily. Improving the description and fidelity of the intervention will support evidence-based practice. Study 3: Objective: To understand which factors can influence satisfaction after RC repair surgery. Methods: Individuals who underwent surgical RC tendon repair completed an online survey. Demographic information, previous and current history were collected with questions about surgical approach, sleep quality, physical therapy treatment, satisfaction, in addition to questionnaires assessing shoulder pain and disability and kinesiophobia. A multiple linear regression was used to investigate the association between the independent variables and the subjects’ satisfaction. Results and conclusion: Sixty-three individuals (59.2±13.6 years, 79.2±12.2 kg, 1.68±0.09 m) participated in the research. Surgery was performed on the dominant side in 54% of subjects, and 38.1% considered themselves much better (+7) on the global of rating of change scale. People with high levels of disability and kinesiophobia were dissatisfied with the surgery.